Cost-benefit analysis of the African risk capacity facility - Clarke, Daniel J.; Hill, Ruth Vargas (International Food Policy Research Institute, 2013)
The African Risk Capacity (ARC), has been proposed as a pan-Africa drought risk pool to insure against drought risk in Africa south of the Sahara. If fully operationalized, the ARC will mark a major change in how donors fund emergency support to countries in Africa during times of need. In this paper, we undertake a cost-benefit analysis of the ARC pool and discuss how lessons can inform the design of the ARC.